2014
DOI: 10.1016/j.vetpar.2014.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and mode of action of afoxolaner, a new isoxazoline parasiticide for dogs

Abstract: Afoxolaner is an isoxazoline compound characterized by a good safety profile and extended effectiveness against fleas and ticks on dogs following a single oral administration. In vitro membrane feeding assay data and in vivo pharmacokinetic studies in dogs established an afoxolaner blood concentration of 0.1-0.2 μg/ml to be effective against both fleas (Ctenocephalides felis) and ticks (Dermacentor variabilis). Pharmacokinetic profiles in dogs following a 2.5mg/kg oral dosage demonstrated uniform and predictab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(127 citation statements)
references
References 11 publications
3
118
0
6
Order By: Relevance
“…However, this general approach merits further study with alternative compounds acting as tick development inhibitors or systemic acaricides. For example, afoxolaner and fluralaner—recently described compounds belonging to a group of systemic insecticides and acaricides termed isoxazolines (Gassel et al 2014, Shoop et al 2014)—were demonstrated to disrupt feeding of I. scapularis adults on orally treated dogs for at least 4 wk (Mitchell et al 2014, Williams et al 2015). Such compounds could prove useful as systemic acaricides offered via oral baits in rodent bait boxes to reduce infestation by I. scapularis immatures on rodent reservoirs.…”
Section: Suppression Of I Scapularis and B Burgdorferi With A Singlmentioning
confidence: 99%
“…However, this general approach merits further study with alternative compounds acting as tick development inhibitors or systemic acaricides. For example, afoxolaner and fluralaner—recently described compounds belonging to a group of systemic insecticides and acaricides termed isoxazolines (Gassel et al 2014, Shoop et al 2014)—were demonstrated to disrupt feeding of I. scapularis adults on orally treated dogs for at least 4 wk (Mitchell et al 2014, Williams et al 2015). Such compounds could prove useful as systemic acaricides offered via oral baits in rodent bait boxes to reduce infestation by I. scapularis immatures on rodent reservoirs.…”
Section: Suppression Of I Scapularis and B Burgdorferi With A Singlmentioning
confidence: 99%
“…Several types of evidence establish that isoxazolines [57][58][59][60][61][62][63][64][65][66] and meta-diamides (including mDA-7 [24,67] and BPB-1 [68]) are NCAs but at a different high affinity site(s) than those for compounds acting at the NCA-IA, NCA-IB and AVE targets ( …”
Section: Nca Actionmentioning
confidence: 99%
“…A 2012 compilation considering the chronology and numbers for introduction of the current insecticides gave the GABA-R targeting compounds as only 1.7% of the total with half of them introduced by 1955 [81]. Newly introduced GABAergic insecticides are flu and afoxolaner used for flea and tick control on cats and dogs [58,[62][63][64][65]. There are also important crop pests highly sensitive to NCA-IIs [24,60,82] indicating possible expanded use on optimization.…”
Section: Prospectsmentioning
confidence: 99%
“…The present study describes the results of an experimental study to assess the efficacy of afoxolaner , a new insecticide-acaricide administered orally in a soft chewable formulation (Nexgard®, Merial), against D. reticulatus infected with Babesia canis in dogs. Afoxolaner belongs to a new class of insecticides-acaricides, the isoxazoline [22], acting systemically through oral formulation [23]. Afoxolaner is highly bound to plasmatic proteins and it is ingested by the hematophagous arthropods during their blood meal.…”
Section: Introductionmentioning
confidence: 99%